Emotional Labor and Perceived Organizational Support as a Predictor of Restaurant Employee Satisfaction - Aulia Aulia; Asma Nur Aina; Zaenal Wafa (Journal of Educational, Health and Community Psychology, 2022)
Many factors affect employee job satisfaction. However, research in the service sector is still rarely found, especially those relating to emotional labor and perceived organizational support. Therefore, this study aims to examine whether emotional labor and perceived organizational support are predictors of job satisfaction for restaurant employees. The method used in this research is a cross-sectional study. Participants in this study were 63 employees at a restaurant in Yogyakarta. The instruments used in data collection in this study were the Job Descriptive Index (JDI) scale, the emotional labor scale, and the perceived organizational support scale. The analysis method used in this research is multiple linear regression analysis. The research results and conclusions indicate that emotional profit and perceived organizational support are predictors of job satisfaction for restaurant employees.